Relationship between anxiety symptoms and physical activity among adolescent girls in Iceland - Kristey Lilja Valgeirsdóttir 1994- (2017)
The main focus of this study is anxiety symptoms among adolescent girls and what effect physical activity may have on anxiety symptoms. Mixed methods research design was used in this study. Quantitative research was used to measure whether frequency of physical activity is linked to the girls’ anxiety symptoms. Data from Icelandic Centre for Social Research and Analysis (ICSRA), Youth in Iceland 2016 was used. Participants were a random sample of total 2000 elementary school students in 8th -10th grade in Iceland. The hypothesis was that girls that are physically inactive report more anxiety symptoms than the girls that are more physically active. The results provided that girls that participate in organized sports 1-3 times a week or 4 times or more a week report significant less anxiety symptoms than those who are physically inactive. There was no significant difference between participating 1-3 times a week and 4 times or more a week. Qualitative research was used to examine professionals’ experiences of adolescent girls’ anxiety symptoms. Participants were two coaches and one educational- and vocational counselor. All of them had experienced girls’ anxiety through their work. In conclusion, physically active girls report better mental health than physically inactive girls. Key words: adolescent girls, anxiety symptoms, physical activity, organized sports participation. Markmið rannsóknarinnar er að skoða kvíðaeinkenni hjá unglingsstúlkum og hvaða áhrif hreyfing hefur á kvíðaeinkennin. Blandað rannsóknarsnið var notað í þessari rannsókn. Í megindlega hluta verkefnisins var notast við úrtak úr spurningakönnun Rannsókna og greiningar, Ungt fólk 2016. Úrtakið samanstóð af 2000 nemendum í 8.-10. bekk grunnskóla landsins. Skoðað var hvort tíðni hreyfingar hefði áhrif á kvíðaeinkenni stúlknanna og var tilgáta rannsóknarinnar sú að þær stúlkur sem eru óvirkar í hreyfing greini frá fleiri kvíðaeinkennum en þær stúlkur sem eru virkar í hreyfingu. Niðurstöður rannsóknarinnar sýndu að þær stúlkur sem tóku virkan þátt ...